Mechanisms of Action of Brief Alcohol Interventions Remain Largely Unknown – A Narrative Review - Gaume, Jacques; McCambridge, Jim; Bertholet, Nicolas; Daeppen, Jean-Bernard (Frontiers in Psychiatry, 2014)
A growing body of evidence has shown efficacy of brief intervention (BI) for hazardous and harmful alcohol use in primary health care settings. Evidence for efficacy in other settings, and effectiveness when implemented at larger scale is disappointing. Indeed, BI comprises varying content, and exploring BI content and mechanisms of action may be a promising way to enhance efficacy and effectiveness. We searched Medline and PsychInfo, as well as references of retrieved publications for original research or reviews on active ingredients (or components, or mechanisms) of face-to-face BIs (and its subtypes, including brief advice and brief motivational interviewing [BMI]) for alcohol. Overall, BI active ingredients have been scarcely investigated, almost only within BMI, and mostly among Emergency Room patients, young adults, and US college students. This body of research has shown that personalized feedback may be an effective component; specific MI techniques showed mixed findings; decisional balance findings tended to suggest a potential detrimental effect; while change plan exercises, advice to reduce or stop drinking, presenting alternative change options, and moderation strategies are promising but need further study. Client change talk is a potential mediator of BMI effects; change in norm perceptions and enhanced discrepancy between current behavior and broader life goals and values have received preliminary support; readiness to change was only partially supported as a mediator; while enhanced awareness of drinking, perceived risks/benefits of alcohol use, alcohol treatment seeking, and self-efficacy were seldom studied and have as yet found no significant support as such. Research is obviously limited and has provided no clear and consistent evidence on the mechanisms of alcohol BI. How BI achieves the effects seen in randomized trials remains mostly unknown and should be investigated to inform the development of more effective interventions.